An overview of implemented and planned policy instruments to decarbonize basic material industries in Germany - Tobias Fleiter; Meta Thurid Lotz; Marlene Arens; Barbara Schlomann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
The policy mix for industry decarbonization in Germany currently undergoes substantial changes. While in the past, it focused strongly on measures supporting and regulating energy efficiency, while in recent years instruments were added that aim at deep decarbonization of industrial production processes and at the long-term transformation of the industry sector. This report presents a summary of the policy instruments aimed at decarbonizing the basic material industry sector in Germany considering currently implemented and planned policies. We provide detailed fact sheets with the current policy design. There is a particular focus on policies supporting innovation and the market entry of new emerging technologies in the following fields, which are regarded central for industry decarbonisation:* hydrogen use, * electrification of industrial heat production, * carbon capture and storage, * bio-based materials, * recycling of materials. Furthermore, we present a summary of the policy mix and discuss its effectiveness to induce the needed technological change towards CO2-neutrality in heavy industry. Current gaps in the policy mix are identified and recommendations to reform the policy mix are provided.
urn:nbn:de:0011-n-6352627
Keywords: 330; industry transformation; decarbonisation; policy mix